A Rare Sigmoid-Colon Schwannoma in a Premenopausal Woman: A Case Report - Selntigia, Aikaterini; Neri, Benedetto; Russo, Consuelo; Martire, Francesco Giuseppe; Soreca, Giorgia; Biasutto, Dario; Di Matteo, Francesco Maria; Exacoustos, Caterina (Acta medica Lituanica, 2023)
Background. Schwannomas of the gastrointestinal tract are a rare type of spindle cell tumor of peripheral nerve. Commonly, schwannomas are discovered incidentally, as they are usually asymptomatic. Case. 46-year-old female patient, suffering from secondary amenorrhea and nonspecific intermittent pelvic pain associated with constipation. During gynecological visit an ultrasonographic systematic transvaginal examination was performed. At the sigmoid-rectal level an intraluminal solid mass was described and an urgent colonoscopy was prescribed. Endoscopic submucosal dissection was performed with en-bloc resection. On immunohistochemical analysis, S100 was strongly positive in tumor cells. Finally, a benign schwannoma of the sigmoid colon was diagnosed. Conclusion. Our case highlights the importance of an adequate transvaginal pelvic examination with the evaluation of all pelvic organs. It could be challenging to make diagnosis in an early stage on asymptomatic patients.